Horizons for Modern Electrochemistry Related to Energy Storage and Conversion, a Review. Issue 1 (3rd March 2021) - Malka, David; Attias, Ran; Shpigel, Netanel; Malchick, Fyodor; Levi, Mikhael D.; Aurbach, Doron
Abstract: The purpose of this paper is to suggest frontier inter‐disciplinary research directions that can be considered as important horizons of modern electrochemistry in the field of energy storage and conversion. We selected several topics that call for advancements in solid‐state, interfacial, analytical and energy‐related electrochemical science. A dramatic improvement in the performance of energy storage and conversion devices is needed to meet the urgent demands of our society. Significantly more efficient devices are needed to meet two major challenges: electro‐mobility, namely electrochemical propulsion of electric vehicles, and the ability to store and convert large quantities of energy generated from sustainable sources such as sun and wind. We suggest promotion of breakthroughs in several important directions. The examples chosen include: Development of novel in‐situ methodologies for design and testing composite electrodes for advanced energy storage devices; Improving the electrochemical performance of high specific capacity, but hard to control, LiNiO2 cathodes for advanced lithium ion batteries designed for electric vehicles, with a quantitative goal of stable specific capacity >230 mAh/g with a charging potential lower than 4.3 V; Advancing aqueous electrochemical systems for large energy storage based on sodium electrochemistry; Promoting development of batteries based on multivalent active metals with magnesium as the most advanced example. There is a strong incentive to promote fundamental and practical progress in the field of rechargeable Mg batteries using new electrodes' configurations and advanced electroanalytical methods. All these directions require deep efforts in basic, fundamental studies, in order to reach important practical goals. Abstract :